KAJIAN METAMORFOSIS PERFORMANCE ART SERTA ASPEK SOSIALNYA (Jurnal Desain Komunikasi Visual Nirmana, 2009)
In the middle of recent development of Indonesian contemporary fine arts world, primarily works regarding the development of technology, New Media Art is one of examples. In the arts context, its uses are often understood as an offer of novel possibility in creating or experiencing the arts. One of them is the metamorphoses of performance art to be multimedia performance, and last metamorphoses into video performance. Video performance, was born out of long history of performance art progress around 1909 through the manifesto of Futurist group in Paris, whose members were poets, painters, and theater players, by using human body as a medium, performance art did dematerialization within art. Video performance in its presentation, perceived that human body was not anymore to be its part, however, what emerged then was virtual body. The existence of body was not really actual, however, its presence could be felt from the visual display coming out from a projector. Here, performance art has been mediated and metamorphosed. In addition, the problems of art and technological fusion promoting the metamorphoses of performance art to be video performance like mentioned above, this writing also discusses social aspects in the line with the emergence and development of performance art in Indonesia. At first, performance art as a process of making aware and resistance arts by deconstructing social reality and the state of being established of the fine arts itself. Second, the ambient media phenomenon in the global advertising practice (including Indonesia) distracting struggle direction of performance art “genue” from the process of making aware media into “kitsch” art as a frontline point of advertising for market interest.Abstract in Bahasa Indonesia:Dalam perkembangan dunia seni rupa kontemporer Indonesia dewasa ini, khususnya karya-karya yang bersinggungan dengan perkembangan teknologi, New Media Art (seni media baru) adalah salah satu contohnya. Dalam konteks seni, penggunaannya sering dipahami sebagai tawaran kemungkinan baru dalam menciptakan atau mengalami kesenian. Salah satunya adalah adanya metamorfosis performance art menjadi multimedia performance dan yang terakhir bermetamorfosis menjadi video performance. Video performance, lahir dari sejarah panjang perkembangan performance art sekitar tahun 1909 lewat manifesto kelompok Futurist di Paris yang beranggotakan penyair, pelukis, dan pemain teater, dengan menggunakan tubuh sebagai medium, performance art melakukan dematerialisasi dalam seni. Video performance dalam presentasinya, tubuh sudah tidak lagi menjadi bagian, tetapi yang hadir kemudian adalah tubuh yang virtual (maya). Kehadiran tubuh tidak benar-benar nyata, tetapi kehadirannya dapat terasa dari tampilan visual yang keluar dari projector. Di sini, performance art telah termediasi dan bermetamorfosa. Selain persoalan fusi seni dan teknologi yang mendorong metamorfosis performance art menjadi video performance seperti di atas, tulisan ini juga membahas aspek-aspek sosial seiring kemunculan dan perkembangan performance art di Indonesia. Pertama performance art sebagai seni penyadaran dan perlawanan dengan mendekonstruksi realitas sosial dan kemapanan seni rupa itu sendiri. Kedua adanya fenomena ambient media dalam praktik periklanan global (termasuk Indonesia) yang membelokkan arah perjuangan ”genue” performance art dari media penyadaran menjadi seni ”kitsch” sebagai ujung tombak periklanan untuk kepentingan pasar.Kata kunci: performance art, video art, seni media baru, ambient media.